Perspektif Kekuatan Lansia di LKS-LU Payung Besurek Kota Bengkulu - Jenike, Bella; Tamrin Bangsu; Indria Agustina (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The growth of the elderly population reaching 12% requires efforts that not only focus on weaknesses, but also the potential of the elderly. This study aims to describe the potential and strengths of the elderly, analyze the role of LKS LU Payung Besurek in implementing the Strengths Perspective and the Asset-Based Community Development (ABCD) model in assisting the elderly. The research approach uses descriptive qualitative, six people consisting of; the head of the institution, social workers, and four assisted elderly determined by purposive sampling technique. Data collection uses interviews, observation, and documentation. Data analysis uses the Miles and Huberman model, namely, the results of the study show that the assisted elderly LKS LU have physical, economic, social, spiritual, and psychological potential. The elderly are still able to work simply, are active in religious, social, economic activities and have good life motivation.The institution plays a role through spiritual, social, health, and economic development, including skills training. The Strengths Perspective approach is seen in efforts to explore and strengthen the potential of the elderly, while the application of the ABCD model is reflected in five principles: community leadership, social relationships, asset utilization, place-based, and inclusion without discrimination. This study concludes that the eld erly can remain independent, productive, and empowered if they receive support from institutions, families, and the social environment.